MENINGKATKAN KONSENTRASI BELAJAR SISWA KELAS V MELALUI METODE BRAIN GYM DI SEKOLAH DASAR Penelitian Tindakan Kelas pada Pembelajaran IPAS di Kelas V UPT SDN 009 Simpang Kubu - Adisti, Anita Mutiara; Witarsa, Ramdhan; Nurmalina, Nurmalina; Fauziddin, Moh; Marleni, Lusi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This research is motivated by the low learning concentration of fifth-grade students at UPT SDN 009 Simpang Kubu. This study aims to describe the planning, implementation, and improvement of the Brain Gym method in enhancing student learning concentration. The research method used is classroom action research. This study was conducted in one cycle with two meetings, where each meeting went through four stages namely the planning, implementation, observation, and reflection stages. The subjects of this study were 15 fifth-grade students of UPT SDN 009 Simpang Kubu, consisting of 7 male students and 8 female students. The research results showed an increase in student learning concentration from the pre-action to cycle 1 meeting 1 by 0,72%. The increase in student learning concentration also showed an increase from cycle 1 meeting 1 to cycle 1 meeting 2 by 4,28%. The conclusion of this study is that there was an overall increase in student learning concentration of 2,86%. The Brain Gym method should continue to be implemented to improve elementary school student learning concentration. Teachers need continuous assistance to implement the Brain Gym method according to the recommended steps.